2018
DOI: 10.1021/acs.macromol.7b02750
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Thermally Induced Cross-Link in C-Linked Methyl Ester-Functionalized Polydicyclopentadiene (fPDCPD)

Abstract: Polydicyclopentadiene (PDCPD) is a durable, highly cross-linked material that is used industrially for the production of automotive body panels among other applications. We recently described a novel C-linked, ester-functionalized polydicyclopentadiene (fPDCPD) that introduces a tunable surface energy and increased T g, without sacrificing the desirable thermal stability of the parent polymer. In this report, we describe an extensive spectroscopic study aimed at the rigorous characterization of the structure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 44 publications
5
33
2
Order By: Relevance
“…In our previous mechanistic studies, 19 we confirmed that the principal crosslinking mechanism for 2 does not take place via secondary metathesis events of the type that are generally considered for unfunctionalized polydicyclopentadiene [49][50][51][52][53] but rather through a self-initiated, head-tail radical polymerization event that occurs through the methacrylate motif embedded within 2 (Scheme 1a). In order to achieve robust attachment of f PDCPD to glass slides, we further exploited this mechanism by carrying out the thermal curing event on the 3-(trimethoxy silyl)propyl methacrylate-coated slide, with the goal of engaging the methacrylate groups in the surface-activating reagent directly in the self-initiated radical polymerization event that occurs across the methacrylate groups in linear polymer 2, resulting in the formation of strong covalent bonds that serve to link the f PDCPD polymer to the glass slide.…”
Section: Resultssupporting
confidence: 80%
See 4 more Smart Citations
“…In our previous mechanistic studies, 19 we confirmed that the principal crosslinking mechanism for 2 does not take place via secondary metathesis events of the type that are generally considered for unfunctionalized polydicyclopentadiene [49][50][51][52][53] but rather through a self-initiated, head-tail radical polymerization event that occurs through the methacrylate motif embedded within 2 (Scheme 1a). In order to achieve robust attachment of f PDCPD to glass slides, we further exploited this mechanism by carrying out the thermal curing event on the 3-(trimethoxy silyl)propyl methacrylate-coated slide, with the goal of engaging the methacrylate groups in the surface-activating reagent directly in the self-initiated radical polymerization event that occurs across the methacrylate groups in linear polymer 2, resulting in the formation of strong covalent bonds that serve to link the f PDCPD polymer to the glass slide.…”
Section: Resultssupporting
confidence: 80%
“…Understanding the chemical properties of a novel material is paramount to discovering its possible future applications. Although some of the unique properties of f PDCPD have been reported previously by our group, [18][19][20] the degree to which the surface can be further functionalized is not yet completely understood. For example, while previous work has shown that partial hydrolysis of the ester functional groups on the surface of f PDCPD can raise the surface energy, 18 we have not yet examined the installation of other functionality at this position.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations